The Easter Vigil in the British Methodist Church: exploring a liturgical enigma - Cooper, Steven R. M. (Joint liturgical studies, 2023)
Regarded in the Catholic tradition as 'the most solemn and splendid of the Church's liturgies', the Easter Vigil liturgy was first published as an authorised Methodist service in Britain in the 1999 Methodist Worship Book. But does the Easter Vigil make sense as a Methodist service? Through the lens of liturgical theology, this study takes us on a journey to identify what makes worship 'Methodist', and investigates how the Easter Vigil liturgy accords with that. We explore the practice of John Wesley, founder of Methodism, at Easter; and by a process of liturgical detective work, we investigate the rationale behind the Easter Vigil's inclusion in The Methodist Worship Book and the process by which it was developed. Ultimately we draw conclusions about the Easter Vigil's appropriateness to Methodist worship, and make recommendations concerning its future development. -- From the back cover